A study on smart parking guidance algorithm - Shin, Jong-Ho; Jun, Hong-Bae (Transportation research. Part C, Emerging technologies, 2014)
•The smart parking guidance algorithm which considers dynamic circumstances of parking facilities in a city.•The heuristic parking guidance algorithm based on dispatching rules.•The validation of the proposed algorithm is performed by the simulation tests.•The proposed algorithm can improve performance measures such as driving duration and time.•The proposed algorithm enables car drivers to find the most appropriate parking lot and reduce redundant time and energy. Parking problem becomes one of major issues in the city transportation management since the spatial resource of a city is limited and the parking cost is expensive. Lots of cars on the road should spend unnecessary time and consume energy during searching for parking due to limited parking space. To cope with these limitations and give more intelligent solutions to drivers in the selection of parking facility, this study proposes a smart parking guidance algorithm. The proposed algorithm supports drivers to find the most appropriate parking facility considering real-time status of parking facilities in a city. To suggest the most suitable parking facility, several factors such as driving distance to the guided parking facility, walking distance from the guided parking facility to destination, expected parking cost, and traffic congestion due to parking guidance, are considered in the proposed algorithm. To evaluate the effectiveness of the proposed algorithm, simulation tests have been carried out. The proposed algorithm helps to maximize the utilization of space resources of a city, and reduce unnecessary energy consumption and CO2 emission of wandering cars since it is designed to control the utilization of parking facility efficiently and reduce traffic congestion due to parking space search.